Fiscal Policy, Uncertainty and Output Growth in Uganda: 1980-2020 - Ssebulime, Kurayish; Mukisa, Ibrahim (East African Journal of Business and Economics, 2023)
Does uncertainty necessarily change the way in which fiscal policy affects output growth in Uganda? We provide an empirical response to this fundamental question using the latest datasets and a rigorous econometric practice. Fiscal policy is often manipulated in many countries as one of the means to provide counter-cyclical stimulus over the cycle of uncertainties. Indeed, fiscal policy operations frequently vary with uncertainty sequence and this introduces bidirectional interactions between fiscal policy, uncertainty and output growth. Using the Autoregressive Distributed Lag Model, we show that tax revenue and expenditure are the most affected fiscal policy measures in the presence of uncertainty, while borrowing is the least affected both in the short and long-run. Therefore, unless government macroeconomic frameworks fully incorporate economic uncertainties into projections, the fragility of rising global and domestic uncertainty is bound to cause large and significant divergencies between the anticipated and the actual growth outturn. We therefore recommend the need to use borrowing avenue in the most optimal means to stimulate and sustain growth. While tax revenues have proved to spur growth both in the short and the long-run, the impact is bound to shrink in the face of uncertainty.